2011
DOI: 10.1167/11.3.18
|View full text |Cite
|
Sign up to set email alerts
|

The effect of contrast intensity and polarity in the achromatic watercolor effect

Abstract: The watercolor effect (WCE) is a filling-in phenomenon in a region demarcated by two thin abutting lines. The perceived chromaticity of the region is similar to that of the interior line. We develop a series of achromatic WCE stimuli to induce lightness changes analogous to the induced chromaticity in the chromatic version of the WCE. We use a variation of the paired-comparison paradigm to quantify the induced lightness of the filled-in regions to regions with real luminance variations. The luminance of the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
38
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(49 citation statements)
references
References 18 publications
10
38
1
Order By: Relevance
“…Free viewing has been used to study the WCE in numerous previous studies (Devinck et al, 2005;Devinck & Spillmann, 2009;Pinna, 1987;Pinna et al, 2001). von der Heydt and Pierson (2006) used a duration of 1 s, not too much shorter than our estimated average duration, and Cao et al (2011) used 150 ms to study an achromatic variant of the WCE.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Free viewing has been used to study the WCE in numerous previous studies (Devinck et al, 2005;Devinck & Spillmann, 2009;Pinna, 1987;Pinna et al, 2001). von der Heydt and Pierson (2006) used a duration of 1 s, not too much shorter than our estimated average duration, and Cao et al (2011) used 150 ms to study an achromatic variant of the WCE.…”
Section: Methodsmentioning
confidence: 99%
“…It is not surprising that in a discrimination experiment, observers might exploit alternative cues, if present. Cao et al (2011) used the degree of inconsistency in judging pairs of stimuli evoking different strengths of an achromatic version of the WCE to demonstrate that the WCE can be quantified. For this method to work, stimuli must be spaced closely enough so that the observer's judgments will be probabilistic, e.g., a given pair (a, b) will, on some trials, be judged a 9 b and on others b 9 a.…”
Section: Observermentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, the color spreading does not involve large brightness changes (Devinck et al, 2005). Recent studies revealed that the achromatic watercolor effect does exist and is measurable, but the magnitude is small (Takashima, 2008; Cao et al, 2011). Regarding the effects of luminance conditions, previous studies showed that the spreading was very weak when the luminance of the outer contour (OC) was in between the luminances of the inner contour (IC) and of the background (Devinck et al, 2005; Cao et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies revealed that the achromatic watercolor effect does exist and is measurable, but the magnitude is small (Takashima, 2008; Cao et al, 2011). Regarding the effects of luminance conditions, previous studies showed that the spreading was very weak when the luminance of the outer contour (OC) was in between the luminances of the inner contour (IC) and of the background (Devinck et al, 2005; Cao et al, 2011). The magnitude of color spreading increased with the luminance ratio of the IC to the OC (Devinck et al, 2005; Devinck and Knoblauch, 2012).…”
Section: Introductionmentioning
confidence: 99%